Effects of oxygenation on the intercalation of 1, 10-phenanthroline-5, 6/4, 7-dione between DNA base pairs: a computational study. Issue 25 (16th June 2017) - Galliot, Aurellia; Gil, Adrià; Calhorda, Maria José
Abstract : The effects of oxygen in positions 4, 7 and 5, 6 of phenanthroline have been studied computationally when this ligand intercalates between DNA base pairs. Our results indicate that solvation energy could be the driving force of the process and thus, it can be also related with the cytotoxicity of the drug. Abstract : The effects of oxygen in positions 4, 7 and 5, 6 of phenanthroline when this ligand intercalates between guanine–cytosine and adenine–thymine DNA base pairs (GC/CG and AT/TA) have been studied at the M06-2X/6-31+G(d, p) level of calculation. We focused on the changes in the structure, stabilization and energy contributions in the analysis of the interaction. The obtained trends in stabilization are explained by a model including repulsive Pauli (Δ E Pauli ) contributions, and attractive dispersion (Δ E disp ), orbital (Δ E orb ) and electrostatic (Δ E elstat ) contributions to energy. When no solvation is considered, the intrinsic Δ E elstat contribution results are crucial for the stabilization of the system. However, the inclusion of the solvation energy Δ E solv can reverse the final stability trend of the systems becoming, thus, the driving force of the process. Therefore, the solvent will have a relevant influence in the potential cytotoxicity of the intercalation drugs.